Knight's Microsoft business intelligence 24-hour trainer leveraging Microsoft SQL server integration, analysis, and reporting services with Excel and SharePoint - Knight, Brian 1976- (Wrox guides, 2010)
Provides information on using the Microsoft business information tools to perform analysis and reporting using Excel and SharePoint.